Spiritual Emotion Freedom Technique (SEFT) untuk Menurunkan Tekanan Darah Lansia dengan Hipertensi: A Systematic Review - Noer Diana Holida; Vivin Nur Hafifah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
Background: Elderly is someone who has reached the age of 65 and is below “old age”. Aging does not automatically lead to disability and dependence. However, a diminished ability to respond to stress. Physical changes due to aging combined with the position of age at high risk of disease and functional impairment cause the elderly to have at least one chronic disease. Objective: The purpose of this systematic review is to determine the effect of Spiritual Emotion Freedom Technique (SEFT) on reducing blood pressure in elderly with hypertension. Methods: Database searches include Google Scholar, Science Direct, and Proquest with the keyword SEFT for lowering blood pressure. The next stage is to select articles according to the criteria, which are published in 2015-2020 with the full text of this Systematic Review using 15 articles that match the inclusion criteria. Results: Spiritual Emotion Freedom Technique (SEFT) therapeutic intervention is a non-pharmacological intervention that is very effective in reducing blood pressure in elderly with hypertension. Conclusion: Spiritual emotional freedom technique (SEFT) intervention is a non-pharmacological intervention that has a strong influence on reducing blood pressure in elderly people with hypertension.Keywords: elderly; hypertension; spiritual emotional freedom technique (SEFT) ABSTRAK Latar Belakang: Lansia merupakan seseorang yang telah berusia 65 tahun berada dibatas bawah “usia tua”. Penuaan tidak secara otomatis menyebabkan kecacatan dan ketergantungan. Namun kemampuan yang berkurang untuk merespons stress. Perubahan fisik karena penuaan dikombinasikan dengan posisi usia pada risiko tinggi penyakit dan kerusakan fungsional menyebabkan lansia mempunyai setidaknya satu penyakit kronis. Tujuan: Tujuan dari SystematicReview ini adalah untuk mengetahui pengaruh Spiritual Emotion Freedom Technique (SEFT) terhadap penurunan tekanan darah lansia dengan hipertensi. Metode: Pencarian database meliputi Google Scholar, Science Direct, dan Proquest dengan kata kunci SEFT untuk penurunan tekanan darah. Tahap berikutnya ialah menyeleksi artikel sesuai batasan kriteria yaitu terbit tahun 2015-2020 dengan teks penuhSystematic Review ini menggunakan 15 artikel yang sesuai dengan kriteria inklusi. Hasil: Intervensi terapi Spiritual Emotion Freedom Technique (SEFT) merupakan intervensi non farmakologis yang sangat evektif dalam penurunan tekanan darah pada lansia dengan hipertensi. Kesimpulan: Intervensi spiritual emotional freedom technique (SEFT) merupakan intervensi non-farmakologis yang sangat berpengaruh terhadap penurunan tekanan darah pada lansia dengan hipertensi.Keywords: lansia; hipertensi; spiritual emotional freedom technique (SEFT)